Development of core-sheath structured smart nanofibers by coaxial electrospinning for thermo-regulated textiles - Yi, Liqiang; Wang, Yan; Fang, Yini; Zhang, Ming; Yao, Juming; Wang, Lina; Marek, Jaromir (RSC advances, 2019)
It is of great significance to develop phase change materials (PCMs) with high performance. The reported PCMs usually possess serious defects like low heat capacity and poor thermal stability. Here, core-sheath structured nanofibers with polyvinyl butyral (PVB) as the sheath and octadecane as the core were fabricated by melt coaxial electrospinning. Pure octadecane without any solvents was used as the core solution, thus, the optimal sample possessed very high latent heat up to 118 J g-1. We studied the influence of core feed rate and PVB solution concentration on the encapsulation rate, and the highest encapsulation rate was found when the PVB concentration was 10% and core feed rate was 0.08 mL h-1. And hexagonal cesium tungsten bronze (Cs x WO3, a near infrared absorber) was introduced into the optimal sample partly to improve its conversion efficiency of solar to thermal energy, and partly absorb uncomfortable infrared light; the composite phase change material also possessed high latent heat up to 96.9 J g-1. In addition, 100 thermal cycle test proved that with a minor latent heat decrease, the prepared core-sheath structured smart nanofibers had good thermal stability, which overcomes the leakage problem of pure octadecane. Additionally, the 9 wt% Cs x WO3-loaded sample had an increase in tensile strength and elongation compared with the sample without Cs x WO3, indicating the good compatibility between Cs x WO3 and PVB.